Photoelectric Vilnius Photometry of Stars in the Mega Proper Motion Field KA 10 - Bartašiutė S. (Open Astronomy, 2003)
Photoelectric seven-color photometry in the Vilnius medium-band, system is obtained for 87 stars down to V≃13.0 in the Kiev proper motion field KA10 [l = 137°, b = -59°]. The size of the field is 1.4 square degrees. For each star, photometric spectral type, absolute magnitude, metallicity, and color excess due to interstellar reddening have been determined. These data, together with previous Vilnius photometry obtained in other seven KA fields at high Galactic latitudes, will be combined with radial-velocity measurements and available proper motions to yield space velocities and to investigate kinematical and chemical properties of the Galactic disk in the direction perpendicular to the Galactic plane.